Male apoE*3‐Leiden.CETP mice on high‐fat high‐cholesterol diet exhibit a biphasic dyslipidemic response, mimicking the changes in plasma lipids observed through life in men. Issue 19 (16th October 2017) - Paalvast, Yared; Gerding, Albert; Wang, Yanan; Bloks, Vincent W.; van Dijk, Theo H.; Havinga, Rick; Willems van Dijk, Ko; Rensen, Patrick C. N.; Bakker, Barbara M.; Kuivenhoven, Jan Albert; Groen, Albert K.
Abstract: Physiological adaptations resulting in the development of the metabolic syndrome in man occur over a time span of several decades. This combined with the prohibitive financial cost and ethical concerns to measure key metabolic parameters repeatedly in subjects for the major part of their life span makes that comprehensive longitudinal human data sets are virtually nonexistent. While experimental mice are often used, little is known whether this species is in fact an adequate model to better understand the mechanisms that drive the metabolic syndrome in man. We took up the challenge to study the response of male apoE*3‐Leiden.CETP mice (with a humanized lipid profile) to a high‐fat high‐cholesterol diet for 6 months. Study parameters include body weight, food intake, plasma and liver lipids, hepatic transcriptome, VLDL – triglyceride production and importantly the use of stable isotopes to measure hepatic de novo lipogenesis, gluconeogenesis, and biliary/fecal sterol secretion to assess metabolic fluxes. The key observations include (1) high inter‐individual variation; (2) a largely unaffected hepatic transcriptome at 2, 3, and 6 months; (3) a biphasic response curve of the main metabolic features over time; and (4) maximum insulin resistance preceding dyslipidemia. The biphasic response in plasma triglyceride and total cholesterol appears to mimic that of men in cross‐sectional studies. Combined, these observations suggest that studies such as these can help to delineate the causes of metabolic derangements in patients suffering from metabolic syndrome. Abstract : We followed male apoE*3‐Leiden.CETP mice on high‐fat high‐cholesterol diet over time and monitored the changes in important parameters of metabolic syndrome. We observed that changes in dyslipidemia were biphasic in nature, which is reminiscent of findings in aging humans. Male apoE*3‐Leiden.CETP mice may be a good model to study age‐related changes in dyslipidemia.